Skin compatibility of two ethanol based virucidal hand disinfectants - Meyer, Bernhard; Matthies, Wolfgang; Nicholson, Joseph E.; Shelanski, Morris V. (International Journal of Infection Control, 2010)
Two virucidal hand rubs containing high concentrations of ethanol were evaluated for their irritating and sensitizing propensities in a Human Repeated Insult Patch Test (HRIPT). Whereas the numbers of responses elicited by Product A and an ethanol control were commensurately low and not significantly different (p<0.256), the number elicited by Product B was significantly higher than those elicited by either Product A or control (p<0.001). Product A was found to be devoid of clinically significant irritating propensities; Product B, a weak cumulative irritant. It was shown that it is possible to use high concentrations of ethanol in formulating highly effective virucidal hand disinfectants without compromising the skin compatibility of the product.